2019
DOI: 10.1039/c9nr01133a
|View full text |Cite
|
Sign up to set email alerts
|

O2 as a molecular probe for nonradiative surface defects in CsPbBr3 perovskite nanostructures and single crystals

Abstract: Surface defects and environmental conditions affect the physical properties of CsPbBr3 perovskites differently, based on the materials dimensionality, despite their ‘defect tolerant’ electronic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 74 publications
3
35
0
Order By: Relevance
“…Despite this, the effects of the environment on the optical properties of lead halide perovskites NCs have been surprisingly poorly investigated to date, with only few experiments on CsPbBr 3 nanocubes grown by hot-injection method, curiously finding contradictory results. In particular, the PL intensity in air has been reported to be lower than in vacuum [3,28], or not affected by the environment [27]. These results are different from the ones on single crystals, bulk polycrystalline thin films, and even nanosheets and nanowires [3], all showing a PL intensity enhancement in air.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Despite this, the effects of the environment on the optical properties of lead halide perovskites NCs have been surprisingly poorly investigated to date, with only few experiments on CsPbBr 3 nanocubes grown by hot-injection method, curiously finding contradictory results. In particular, the PL intensity in air has been reported to be lower than in vacuum [3,28], or not affected by the environment [27]. These results are different from the ones on single crystals, bulk polycrystalline thin films, and even nanosheets and nanowires [3], all showing a PL intensity enhancement in air.…”
Section: Introductionmentioning
confidence: 82%
“…In particular, the PL intensity in air has been reported to be lower than in vacuum [3,28], or not affected by the environment [27]. These results are different from the ones on single crystals, bulk polycrystalline thin films, and even nanosheets and nanowires [3], all showing a PL intensity enhancement in air.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…O 2 was then used as a molecular probe to compare and contrast the ability of the proposed ALD modes to grow gas diffusion barriers. Recent reports have demonstrated reduction in the PL of CsPbBr 3 NCs in the presence of molecular O 2 . The authors have suggested that this behavior is due to the interaction of O 2 with the NC surface.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, we optimize the above‐mentioned ALD protection scheme for CsPbBr 3 NC films by using O 2 as a molecular diffusion probe to assess the uniformity of the encapsulating AlO x layer. The O 2 quenches the PL by extracting photogenerated charges . The better the gas barrier properties of ALD layer are, the less quenching is expected when the CsPbBr 3 /AlO x nanocomposites are exposed to an O 2 ‐rich atmosphere .…”
Section: Introductionmentioning
confidence: 99%